Implementasi Pembelajaran Aktif, Kreatif, Efektif dan Menyenangkan pada Mata Pelajaran PAI (Studi Kasus di Kelas X.E7 SMAN 1 Painan) - Defani, Melisa; Wirdati, Wirdati (ANWARUL, 2023)
The problem of this research is how to implement active, creative, effective and fun learning in improving the quality of PAI learning at SMA N 1 Painan, beceuase there are still many conventional learning implementasions. The research method used is qualitative research which refers to the problem study approach and the focus or core of this research is to see and know how teachers are able to create an active, creative, effective and fun learning atmosphere in PAI subjects. Then for the types of data that exits in this study are data in the from of primary data and secondary data, while the information obtained is data generated from observasion in the field and also interwiws with informants. The informants selected by the researcher included : Deputy Curriculum, Teachers who teach in class X.E7 an students in class X.E7 SMA N 1 Painan. As for the result, the researchers found that the PAKEM learning model was able to improve student learning outcomes.